Return Saham Kepemilikan Institusional, Dividen, dan Return Saham: Peran Kinerja Lingkungan - Sitepu, Yuni Lestari Br; Sitepu, Immanuelta; Silalahi, Mutiara (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2024)
This study focuses on the influence of environmental performance, institutional ownership, dividend policy, and accounting profit on stock returns in manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. Using a purposive sampling method, researchers gathered 54 data points which were then processed with SPSS and analyzed through panel data regression. The results reveal a significant negative relationship between environmental performance and stock returns. Meanwhile, institutional ownership and accounting profit show a significant positive influence on stock returns. Dividend policy, in contrast, does not exhibit a significant effect. Moreover, this study introduces a moderating variable that may amplify or diminish the link between these independent variables and the dependent variable. These findings highlight the importance of synchronizing environmental performance with financial strategies to bolster corporate value and enhance investment decision-making—especially pertinent in today’s discussions on climate change and renewable energy.